2017
DOI: 10.1007/s10529-017-2337-y
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of microRNA-17-5p ameliorates atherosclerotic lesions in ApoE−/− mice and restores the expression of very low density lipoprotein receptor

Abstract: A novel interaction between miR-17-5p and VLDLR is revealed and suggests that miR-17-5p may be a potential therapeutic target for AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…the present study predicted mir-17-5p binding to MalaT1 using bioinformatics prediction software. our previous studies have shown that mir-17-5p was elevated in patients with aS and also macrophages of apoe -/mice with aS, and that inhibition of miR-17-5p reduced inflammation and lipid accumulation by interacting with aBca1 in aS (19,44). Based on the present bioinformatics prediction and our previous results, the present study investigated the role of MalaT1 on the mir-17-5p/aBca1 axis.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…the present study predicted mir-17-5p binding to MalaT1 using bioinformatics prediction software. our previous studies have shown that mir-17-5p was elevated in patients with aS and also macrophages of apoe -/mice with aS, and that inhibition of miR-17-5p reduced inflammation and lipid accumulation by interacting with aBca1 in aS (19,44). Based on the present bioinformatics prediction and our previous results, the present study investigated the role of MalaT1 on the mir-17-5p/aBca1 axis.…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, MalaT1 may possess an important role in aS; however, the potential molecular mechanism of MalaT1 regulation of cholesterol accumulation in macrophages, which is a key event of aS progression (18), remains to be elucidated. in addition, our previous study has demonstrated that mir-17-5p was highly expressed in the peripheral blood of patients with aS, and the suppression of mir-17-5p could alleviate aS in mice (19). The present study hypothesized that MalaT1 may have a conserved mir-17-5p binding site, and aTP-binding cassette transporter a1 (aBca1) could be a target of mir-17-5p.…”
Section: Introductionmentioning
confidence: 75%
“…Many miRNAs may affect PCSK9 expression 65) . MiR-17-5p, a potential biomarker for the diagnosis of coronary atherosclerosis, inhibits VLDLR expression in vascular SMCs via direct binding to its 3'-UTR 66) . Inhibition of miR-17-5p induces upregulation of VLDLR and downregulation of PCSK9 in atherosclerotic apoE −/− mice 66) .…”
Section: Shear Stress-induced Pcsk9 Expressionmentioning
confidence: 99%
“…Increased miR-17-5p expression induced proliferation and inhibited apoptosis of lung cancer cells, while reduced lung cancer cell sensitivity to Gefitinib [ 14 ]. Besides, miR-17-5p has been considered as a potential therapeutic target for atherosclerotic lesions [ 15 ], retinal inflammation [ 16 ], non-traumatic osteonecrosis of femoral head [ 17 ], and fatty liver [ 18 ]. However, no study has been carried out to explore the role of miR-17-5p in rhinitis.…”
Section: Introductionmentioning
confidence: 99%